Analysis of Voltage Drop and Power Loss in the 20 kV Medium Voltage Network of PT. PLN (PERSERO) ULP Panakkukang Uses ETAP Software - Adrian Pratama; Al Imran; Haripuddin Haripuddin (Fakultas Teknik Universitas Negeri Makassar, 2026)
In the modern era, electrical energy has evolved into an indispensable cornerstone of societal function, particularly in dense urban environments, where infrastructure demands are relentless. Ensuring both the effectiveness and efficiency of energy distribution from generation plants to end consumers is a paramount challenge for utility providers. A significant hurdle in this process is the inevitable phenomenon of energy loss, which degrades system performance and increases operational costs. This study provides a comprehensive analysis of power loss within the medium-voltage distribution network at PT. PLN (Persero) ULP Panakkukang. Several critical factors contribute to these inefficiencies, most notably the load imbalance between phases, which leads to neutral current flow and resistive heating generated within conductors. Furthermore, physical degradation, such as poor conductor connections, acts as a persistent impediment to seamless distribution. To quantify these issues, this research employs a dual-methodology approach: utilizing Electrical Transient Analyzer Program (ETAP) software alongside rigorous manual calculations to measure voltage drop and real power loss. These findings indicate that the losses fluctuate significantly in response to shifting load conditions throughout the day. Ultimately, this research serves as a vital technical reference for optimizing grid performance and enhancing the reliability of future electricity distribution systems.